Investigating service delivery and perinatal outcomes during the low prevalence first year of COVID-19 in a multiethnic Australian population: a cohort study - Vincent W Lee; N Wah Cheung; Dharmintra Pasupathy; Sarah J Melov; James Elhindi; Therese M McGee; Seng Chai Chua; Justin McNab; Thushari I Alahakoon (BMJ Open)
Objective Investigate the impact of the COVID-19 pandemic on perinatal outcomes in an Australian high migrant and low COVID-19 prevalent population to identify if COVID-19 driven health service changes and societal influences impact obstetric and perinatal outcomes.Design Retrospective cohort study with pre COVID-19 period 1 January 2018–31 January 2020, and first year of global COVID-19 period 1 February 2020–31 January 2021. Multivariate logistic regression analysis was conducted adjusting for confounders including age, area-level socioeconomic status, gestation, parity, ethnicity and body mass index.Setting Obstetric population attending three public hospitals including a major tertiary referral centre in Western Sydney, Australia.Participants Women who delivered with singleton pregnancies over 20 weeks gestation. Ethnically diverse women, 66% overseas born. There were 34 103 births in the district that met inclusion criteria: before COVID-19 n=23 722, during COVID-19 n=10 381.Main outcome measures Induction of labour, caesarean section delivery, iatrogenic and spontaneous preterm birth, small for gestational age (SGA), composite neonatal adverse outcome and full breastfeeding at hospital discharge.Results During the first year of COVID-19, there was no change for induction of labour (adjusted OR, aOR 0.97; 95% CI 0.92 to 1.02, p=0.26) and a 25% increase in caesarean section births (aOR 1.25; 95% CI 1.19 to 1.32, p<0.001). During the COVID-19 period, we found no change in iatrogenic preterm births (aOR 0.94; 95% CI 0.80 to 1.09) but a 15% reduction in spontaneous preterm birth (aOR 0.85; 95% CI 0.75 to 0.97, p=0.02) and a 10% reduction in SGA infants at birth (aOR 0.90; 95% CI 0.82 to 0.99, p=0.02). Composite adverse neonatal outcomes were marginally higher (aOR 1.08; 95% CI 1.00 to 1.15, p=0.04) and full breastfeeding rates at hospital discharge reduced by 15% (aOR 0.85; 95% CI 0.80 to 0.90, p<0.001).Conclusion Despite a low prevalence of COVID-19, both positive and adverse obstetric outcomes were observed that may be related to changes in service delivery and interaction with healthcare providers. Further research is suggested to understand the drivers for these changes.